IMPLEMENTASI AUDIO STEGANOGRAFI MENGGUNAKAN ALGORITMA DISCRETE COSINE TRANSFORM - Trihastuti Yuniati (Jurnal Teknoinfo, 2023)
The data exchange is increasingly felt in the era of massive technological developments. This condition results in data requiring a safe path in the delivery process. However, the current condition of the communication system or public internet is not completely secure because there is a possibility of data interception and manipulation by eavesdroppers. One solution to this problem is to apply steganography. Steganography is the science of hiding messages into other media so that people other than the sender and recipient do not know the existence of the message. In this study, the implementation of the steganography method was carried out by hiding text messages in audio files. Audio files are used in this study with the aim of exploiting gaps in human hearing so that the difference between the initial audio and the audio that has been inserted with the message is blurred. The audio type used is wav, because the wav file contains uncompressed audio, so the file will not be damaged after the message is inserted. The use of the Discrete Cosine Transform (DCT) method was chosen because of its ability to maintain the integrity of the messenger file which resulted in the message being difficult to detect in the steganographic file. Implementation is done using Matlab. The test is carried out using the black box testing method and calculating the Peak Signal to Noise Ratio (PSNR) value using a combination of 8 audio files and 3 sound recordings of various sizes with the message inserted in the form of 6 sample messages of type txt and messages typed directly on the form provided. The results of the black box test show that every feature and button installed in the application can function properly. While the results of the message insertion experiment with a total of 88 test scenarios obtained 7 error scenarios and 81 successes. The error occurs because the size of the inserted data is larger than the duration of the audio to be inserted. PSNR calculation results show that 75.31% of audio files after message insertion have PSNR values above 40dB from a total of 81 successful trials. This shows that the output audio file that has been inserted with a message still has good quality.